Composite tubular catalyst as well as preparation method and application thereof

By preparing the composite tubular catalyst, the problem of low removal efficiency of NOx and VOCs at low temperatures was solved, and the effect of efficient removal of NOx and VOCs in the range of 200-350°C was achieved, with good thermal stability and CO2 selectivity.

CN119500285APending Publication Date: 2025-02-25TIANJIN UNIV

Patent Information

Application Number
CN202411646136.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing Ce-Ti catalysts have problems with high synergistic windows and low mineralization rates in NH3-SCR reactions, and it is difficult to efficiently remove NOx and VOCs at low temperatures.

Method used

By using the preparation method of composite tubular catalyst, the composite catalyst obtained has excellent catalytic properties by dissolving the metal salt and titanium salt in deionized water and adding alkali liquid to precipitate.

Benefits of technology

At a temperature of 200-350°C, the composite tubular catalyst can efficiently remove NOx and VOCs, widen the temperature range of the synergistic reaction between nitrogen oxides and volatile organic compounds, and has good thermal stability and CO2 selectivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500285A_ABST
    Figure CN119500285A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of catalysts, in particular to a composite tubular catalyst and a preparation method and application thereof. The preparation method comprises the following steps: adding metal salt and titanium salt into deionized water, stirring and dissolving, then adding alkali liquor to precipitate the mixed solution, aging, and finally washing, drying, grinding and calcining the precipitate to obtain a composite catalyst precursor; and mixing the composite catalyst precursor and a strong alkali solution, performing ultrasonic treatment, stirring, performing hydrothermal reaction, performing acid pickling and water washing on the reacted product, and finally drying, grinding and calcining to obtain the composite tubular catalyst. Wherein the molar ratio of the metal to the titanium is (0.05-0.2): 1. The composite tubular catalyst can efficiently and synergistically remove NOx and VOCs at the temperature of 200-350 DEG C, and the synergistic reaction temperature interval of nitrogen oxides and volatile organic compounds is effectively widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, and in particular to a composite tubular catalyst and a preparation method and application thereof. Background Art

[0002] In recent years, PM 2.5 The pollution of NOx and VOCs is becoming increasingly prominent and has become an important factor affecting air quality. 2.5 NOx and VOCs are common precursors of nitrogen oxides and oxygen. Reducing NOx and VOCs emissions is crucial to improving air quality. Currently, selective catalytic reduction (SCR) and catalytic oxidation are the most widely used flue gas treatment technologies for NOx and VOCs removal, respectively. During the NH3-SCR reaction, reaction conditions allow for the simultaneous catalytic combustion of VOCs. Simultaneous removal of nitrogen oxides and volatile organic compounds (VOCs) can also save energy and reduce costs, facilitating industrial applications. Therefore, it is necessary to rationally improve the design of existing SCR catalysts.

[0003] Toluene, as a typical volatile organic compound, is often accompanied by nitrogen oxide emissions in industrial production. Therefore, research on the simultaneous removal of nitrogen oxides and toluene has mainly focused on modifying V-based and Mn-based catalysts. The poor redox performance of V-based catalysts poses a challenge to their catalytic oxidation of VOCs in low-temperature NH3-SCR reactions. Manganese-based catalysts generally have insufficient resistance to SO2 and, due to their strong redox properties, often produce large amounts of greenhouse gas N2O during the reaction. In contrast, Ce-based catalysts have attracted much attention due to their excellent oxygen storage capacity, moderate redox properties, and other excellent properties.

[0004] Currently, most Ce-Ti catalysts exhibit high catalytic activity in the NH3-SCR reaction, making them suitable materials for the simultaneous removal of nitrogen oxides and toluene. Research on catalysts for the synergistic removal of NOx and VOCs has been plagued by issues such as a high synergistic temperature window (>250°C) and low mineralization rates. Therefore, it is necessary to further lower the VOC conversion temperature of Ce-based catalysts to achieve a highly compatible conversion temperature for both pollutants. Summary of the Invention

[0005] In order to solve the above technical problems, the present invention provides a composite tubular catalyst and its preparation method and application. The composite tubular catalyst can efficiently and synergistically remove NOx and VOCs at a temperature of 200-350°C, effectively broadening the temperature range of the synergistic reaction of nitrogen oxides and volatile organic compounds, and has good application prospects in the direction of synergistic removal of multiple pollutants in flue gas.

[0006] To this end, the present invention provides the following technical solutions:

[0007] In a first aspect, the present invention provides, in an optional embodiment, a method for preparing a composite tubular catalyst, comprising the following steps:

[0008] S1: adding a metal salt and a titanium salt to deionized water and stirring to dissolve them, then adding an alkali solution to cause precipitation in the mixed solution, aging it, and finally washing, drying, grinding and calcining the precipitate to obtain a composite catalyst precursor;

[0009] S2: mixing the composite catalyst precursor and a strong alkaline solution, ultrasonically treating and stirring, and then subjecting them to a hydrothermal reaction. The reaction product is then acid-washed and washed with water, and finally dried, ground and calcined to obtain the composite tubular catalyst;

[0010] Wherein, the molar ratio of the metal to titanium is 0.05-0.2:1.

[0011] Furthermore, the molar ratio of the metal in the metal salt to the titanium in the titanium salt is 0.125:1. The metal in the metal salt is selected from one or more of cerium, vanadium, manganese, iron, or copper; and / or the alkaline solution is selected from one or more of ammonia, sodium hydroxide, ammonium carbonate, or sodium oxalate solution. The aging time is 12-24 hours; and / or the calcination time is 3-5 hours at a temperature of 400-500°C.

[0012] Preferably, in step S2, the strong alkaline solution is one or more of sodium hydroxide or potassium hydroxide solution, with a concentration of 8-12 mol / L; and / or the mass volume ratio of the composite catalyst precursor to the strong alkaline solution is 1 g:20-35 mL. The hydrothermal reaction temperature is 140-180°C and the time is 24-48 hours; and / or the calcination temperature is 400-500°C and the time is 3-5 hours; and / or the acid washing solution is one or more of dilute nitric acid or dilute hydrochloric acid, and the acid washing is performed until the pH value of the reaction product reaches 1-2; and / or the water washing solution is deionized water and ethanol.

[0013] Preferably, in step S2, a surfactant may be added to the strong alkaline solution, wherein the surfactant is hexadecyltrimethylammonium bromide; after the surfactant is added to the strong alkaline solution, the concentration of the surfactant in the mixed solution is 0.001-0.08 mol / L.

[0014] In a second aspect, the present invention provides, in an optional embodiment, a composite tubular catalyst prepared using the above-mentioned preparation method.

[0015] In a third aspect, the present invention provides, in an optional embodiment, an application of the above-mentioned composite tubular catalyst in the simultaneous removal of NOx and VOCs.

[0016] Preferably, the temperature range for simultaneous removal of NOx and VOCs is 100-400°C, preferably 200-350°C.

[0017] Compared with the prior art, the present invention has one of the following beneficial effects:

[0018] 1. The composite tubular catalyst of the present invention achieves NOx and toluene removal efficiencies exceeding 90% at temperatures between 200°C and 350°C, effectively broadening the temperature range for the synergistic reaction of NOx and VOCs. Furthermore, the composite catalyst of the present invention exhibits advantages such as high thermal stability, high CO2 selectivity, and excellent water and sulfur resistance.

[0019] 2. The preparation method of the composite tubular catalyst of the present invention is simple and easy, and the raw materials are green, environmentally friendly and low in price.

[0020] 3. The composite tubular catalyst of the present invention can be used for the synergistic removal of multiple pollutants in flue gas, specifically, it can efficiently and synergistically remove nitrogen oxides and volatile organic compounds. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0022] Figure 1 This is a SEM analysis image of the composite tubular catalyst prepared in Example 3 of the present invention;

[0023] Figure 2 This is a SEM analysis image of the composite tubular catalyst prepared in Comparative Example 3 of the present invention;

[0024] Figure 3 This is a SEM analysis image of the composite tubular catalyst prepared in Comparative Example 4 of the present invention;

[0025] Figure 4 This is a TEM analysis image of the composite tubular catalyst prepared in Example 3 of the present invention;

[0026] Figure 5 TEM analysis diagram of the composite catalyst prepared in Comparative Example 1 of the present invention;

[0027] Figure 6 TEM analysis diagram of the composite catalyst prepared in Comparative Example 2 of the present invention;

[0028] Figure 7 This is a graph showing the activity data of the composite tubular catalyst prepared in Example 3 of the present invention for simultaneously removing NOx and VOCs;

[0029] Figure 8 This is the activity data diagram of the composite catalyst prepared in Comparative Example 1 of the present invention for simultaneously removing NOx and VOCs;

[0030] Figure 9 This is the activity data diagram of the composite catalyst prepared in Comparative Example 2 of the present invention for simultaneously removing NOx and VOCs;

[0031] Figure 10 This is the activity data diagram of the composite catalyst prepared in Comparative Example 3 of the present invention for simultaneously removing NOx and VOCs;

[0032] Figure 11 This is the activity data diagram of the composite catalyst prepared in Comparative Example 4 of the present invention for simultaneously removing NOx and VOCs;

[0033] Figure 12 This is a comparison chart of NOx activity under synergistic working conditions for the composite tubular catalysts prepared in Examples 1-6 of the present invention;

[0034] Figure 13 This is a comparison chart of VOCs activity under synergistic working conditions of the composite tubular catalysts prepared in Examples 1-6 of the present invention;

[0035] Figure 14 A comparison of N2 selectivity for simultaneous removal of NOx and VOCs by the catalysts prepared in Examples 1-6 of the present invention and Comparative Examples 1-4;

[0036] Figure 15 This is an activity data diagram of the composite tubular catalyst prepared in Example 3 of the present invention for simultaneously removing NOx and CVOCs;

[0037] Figure 16 This is a stability data diagram of the composite tubular catalyst prepared in Example 3 of the present invention;

[0038] Figure 17 This is a data graph of the water resistance performance of the composite tubular catalyst prepared in Example 3 of the present invention;

[0039] Figure 18 This is a graph showing the sulfur resistance and water resistance performance of the composite tubular catalyst prepared in Example 3 of the present invention;

[0040] Figure 19 Schematic diagram of the process for synthesizing the composite tubular catalyst according to Examples 1-4 of the present invention. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0042] The technical solution of the present invention will be described below with reference to the embodiments.

[0043] Example 1

[0044] See also Figure 19 This embodiment provides a method for preparing a composite tubular catalyst, comprising the following steps:

[0045] S1: According to the molar ratio of n(Ce) to n(Ti) = 1:20 in the final sample, cerium nitrate (Ce(NO3)3) and titanium sulfate (Ti(SO4)2) were weighed and added to deionized water. Stirred continuously on a magnetic stirrer at room temperature for 1 hour until fully dissolved to form a precursor solution. Ammonia water was slowly added dropwise to the precursor solution with continuous stirring until the pH value of the solution reached 10 and a precipitate appeared. After aging at room temperature for 12 hours, the resulting precipitate was washed with deionized water until neutral, then dried at 100°C for 12 hours, crushed and sieved, and calcined at 400°C for 5 hours to obtain a dark yellow powder, which is the composite catalyst precursor.

[0046] S2: 2g of the composite catalyst precursor and 40mL of a mixed solution containing 0.5832g of hexadecyltrimethylammonium bromide (CTAB) and NaOH (wherein the concentration of NaOH is 10mol / L) were transferred to a polytetrafluoroethylene liner. After ultrasonic treatment for 30min, the mixture was transferred to a magnetic stirrer and stirred for 1h to mix evenly. The mixture was then placed in a stainless steel reactor and allowed to stand at 150°C and autogenous pressure for 24h to form crystals. After the reaction was completed, the reactor was removed and cooled at room temperature. The resulting product was first washed with dilute nitric acid to a pH of approximately 1.6, then repeatedly washed with deionized water and anhydrous ethanol until neutral, then dried at 80°C for 12h, and finally calcined at 400°C for 3h to obtain a composite tubular catalyst.

[0047] Example 2

[0048] See also Figure 19 This embodiment provides a method for preparing a composite tubular catalyst, comprising the following steps:

[0049] S1: According to the molar ratio of n(Ce) to n(Ti) = 1:10 in the final sample, cerium nitrate (Ce(NO3)3) and titanium sulfate (Ti(SO4)2) were weighed and added to deionized water. Stirred continuously on a magnetic stirrer at room temperature for 1 hour until fully dissolved to form a precursor solution. Ammonia water was slowly added dropwise to the precursor solution with continuous stirring until the pH value of the solution reached 10 and a precipitate appeared. After aging at room temperature for 12 hours, the resulting precipitate was washed with deionized water until neutral, then dried at 100°C for 12 hours, crushed and sieved, and calcined at 400°C for 5 hours to obtain a dark yellow powder, which is the composite catalyst precursor.

[0050] S2: 2g of the composite catalyst precursor and 40mL of a mixed solution containing 0.5832g of hexadecyltrimethylammonium bromide (CTAB) and NaOH (wherein the concentration of NaOH is 10mol / L) were transferred to a polytetrafluoroethylene liner. After ultrasonic treatment for 30min, the mixture was transferred to a magnetic stirrer and stirred for 1h to mix evenly. The mixture was then placed in a stainless steel reactor and allowed to stand at 150°C and autogenous pressure for 24h to form crystals. After the reaction was completed, the reactor was removed and cooled at room temperature. The resulting product was first washed with dilute nitric acid to a pH of approximately 1.6, then repeatedly washed with deionized water and anhydrous ethanol until neutral, then dried at 80°C for 12h, and finally calcined at 400°C for 3h to obtain a composite tubular catalyst.

[0051] Example 3

[0052] See also Figure 19 This embodiment provides a method for preparing a composite tubular catalyst, comprising the following steps:

[0053] S1: According to the molar ratio of n(Ce) to n(Ti) = 1:8 in the final sample, cerium nitrate (Ce(NO3)3) and titanium sulfate (Ti(SO4)2) were weighed and added to deionized water. Stirred continuously on a magnetic stirrer at room temperature for 1 hour until fully dissolved to form a precursor solution. Ammonia water was slowly added dropwise to the precursor solution with continuous stirring until the pH value of the solution reached 10 and a precipitate appeared. After aging at room temperature for 12 hours, the resulting precipitate was washed with deionized water until neutral, then dried at 100°C for 12 hours, crushed and sieved, and calcined at 400°C for 5 hours to obtain a dark yellow powder, which is the composite catalyst precursor.

[0054] S2: 2g of the composite catalyst precursor and 40mL of a mixed solution containing 0.5832g of hexadecyltrimethylammonium bromide (CTAB) and NaOH (wherein the concentration of NaOH is 10mol / L) were transferred to a polytetrafluoroethylene liner. After ultrasonic treatment for 30min, the mixture was transferred to a magnetic stirrer and stirred for 1h to mix evenly. The mixture was then placed in a stainless steel reactor and allowed to stand at 150°C and autogenous pressure for 24h to form crystals. After the reaction was completed, the reactor was removed and cooled at room temperature. The resulting product was first washed with dilute nitric acid to a pH of approximately 1.6, then repeatedly washed with deionized water and anhydrous ethanol until neutral, then dried at 80°C for 12h, and finally calcined at 400°C for 3h to obtain a composite tubular catalyst.

[0055] The composite tubular catalyst obtained in this example was observed by scanning electron microscopy and transmission electron microscopy. Figure 1 and Figure 4 .

[0056] Example 4

[0057] See also Figure 19 This embodiment provides a method for preparing a composite tubular catalyst, comprising the following steps:

[0058] S1: According to the molar ratio of n(Ce) to n(Ti) = 1:6 in the final sample, cerium nitrate (Ce(NO3)3) and titanium sulfate (Ti(SO4)2) were weighed and added to deionized water. Stirred continuously on a magnetic stirrer at room temperature for 1 hour until fully dissolved to form a precursor solution. Ammonia water was slowly added dropwise to the precursor solution with continuous stirring until the pH value of the solution reached 10 and a precipitate appeared. After aging at room temperature for 12 hours, the resulting precipitate was washed with deionized water until neutral, then dried at 100°C for 12 hours, crushed and sieved, and calcined at 400°C for 5 hours to obtain a dark yellow powder, which is the composite catalyst precursor.

[0059] S2: 2g of the composite catalyst precursor and 40mL of a mixed solution containing 0.5832g of hexadecyltrimethylammonium bromide (CTAB) and NaOH (wherein the concentration of NaOH is 10mol / L) were transferred to a polytetrafluoroethylene liner. After ultrasonic treatment for 30min, the mixture was transferred to a magnetic stirrer and stirred for 1h to mix evenly. The mixture was then placed in a stainless steel reactor and allowed to stand at 150°C and autogenous pressure for 24h to form crystals. After the reaction was completed, the reactor was removed and cooled at room temperature. The resulting product was first washed with dilute nitric acid to a pH of approximately 1.6, then repeatedly washed with deionized water and anhydrous ethanol until neutral, then dried at 80°C for 12h, and finally calcined at 400°C for 3h to obtain a composite tubular catalyst.

[0060] Example 5

[0061] This embodiment provides a method for preparing a composite tubular catalyst, comprising the following steps:

[0062] S1: According to the molar ratio of n(Mn):n(Ti)=1:8 in the final sample, manganese nitrate (Mn(NO3)2) and titanium sulfate (Ti(SO4)2) were weighed and added to deionized water. Stirred continuously on a magnetic stirrer at room temperature for 1 hour until fully dissolved to form a precursor solution. Ammonia water was slowly added dropwise to the precursor solution with continuous stirring until the pH value of the solution reached 10 and a precipitate appeared. After aging at room temperature for 12 hours, the resulting precipitate was washed with deionized water until neutral, then dried at 100°C for 12 hours, crushed and sieved, and calcined at 400°C for 5 hours to obtain the composite catalyst precursor.

[0063] S2: 2g of the composite catalyst precursor and 40mL of a mixed solution containing 0.5832g of hexadecyltrimethylammonium bromide (CTAB) and NaOH (wherein the concentration of NaOH is 10mol / L) were transferred to a polytetrafluoroethylene liner. After ultrasonic treatment for 30min, the mixture was transferred to a magnetic stirrer and stirred for 1h to mix evenly. The mixture was then placed in a stainless steel reactor and allowed to stand at 150°C and autogenous pressure for 24h to form crystals. After the reaction was completed, the reactor was removed and cooled at room temperature. The resulting product was first washed with dilute nitric acid to a pH of approximately 1.6, then repeatedly washed with deionized water and anhydrous ethanol until neutral, then dried at 80°C for 12h, and finally calcined at 400°C for 3h to obtain a composite tubular catalyst.

[0064] Example 6

[0065] This embodiment provides a method for preparing a composite tubular catalyst, comprising the following steps:

[0066] S1: According to the molar ratio of n(Cu) to n(Ti) = 1:8 in the final sample, copper nitrate (Cu(NO3)2) and titanium sulfate (Ti(SO4)2) were weighed and added to deionized water. Stirred continuously on a magnetic stirrer at room temperature for 1 hour until fully dissolved to form a precursor solution. Sodium oxalate solution was slowly added dropwise to the precursor solution with continuous stirring until a precipitate appeared in the solution. After aging at room temperature for 12 hours, the resulting precipitate was washed with deionized water until neutral, then dried at 100°C for 12 hours, crushed and sieved, and calcined at 400°C for 5 hours to obtain the composite catalyst precursor.

[0067] S2: 2g of the composite catalyst precursor and 40mL of a mixed solution containing 0.5832g of hexadecyltrimethylammonium bromide (CTAB) and NaOH (wherein the concentration of NaOH is 10mol / L) were transferred to a polytetrafluoroethylene liner. After ultrasonic treatment for 30min, the mixture was transferred to a magnetic stirrer and stirred for 1h to mix evenly. The mixture was then placed in a stainless steel reactor and allowed to stand at 150°C and autogenous pressure for 24h to form crystals. After the reaction was completed, the reactor was removed and cooled at room temperature. The resulting product was first washed with dilute nitric acid to a pH of approximately 1.6, then repeatedly washed with deionized water and anhydrous ethanol until neutral, then dried at 80°C for 12h, and finally calcined at 400°C for 3h to obtain a composite tubular catalyst.

[0068] Comparative Example 1

[0069] This comparative example provides a method for preparing a composite catalyst, comprising the following steps:

[0070] According to the molar ratio of n(Ce) to n(Ti) = 1:8 in the final sample, cerium nitrate (Ce(NO3)3) and titanium sulfate (Ti(SO4)2) were weighed and added to deionized water. The mixture was stirred continuously on a magnetic stirrer at room temperature for 1 hour until it was fully dissolved to form a precursor solution. Ammonia water was slowly added dropwise to the precursor solution and stirred continuously until the pH value of the solution reached 10 and a precipitate appeared. After aging at room temperature for 12 hours, the obtained precipitate was washed with deionized water until it was neutral, then dried at 100°C for 12 hours, crushed and sieved, and then calcined at 400°C for 5 hours to obtain a composite catalyst. The composite catalyst obtained in this comparative example was observed by transmission electron microscopy. The results are shown in FIG. Figure 5 .

[0071] Comparative Example 2

[0072] This comparative example provides a method for preparing a composite catalyst, comprising the following steps:

[0073] According to the molar ratio of n(Ce):n(Ti)=1:8 in the final sample, cerium nitrate (Ce(NO3)3) and titanium dioxide (TiO210-25nm anatase) were weighed and added to deionized water. The mixture was stirred continuously on a magnetic stirrer at room temperature for 12 hours until it was fully impregnated. It was then dried at 100°C for 12 hours, rolled and sieved, and then calcined at 400°C for 5 hours to obtain a composite catalyst. The composite catalyst obtained in this comparative example was observed by transmission electron microscopy. The results are shown in Figure 2. Figure 6 .

[0074] Comparative Example 3

[0075] This comparative example provides a method for preparing a composite tubular catalyst, comprising the following steps:

[0076] S1: According to the molar ratio of n(Ce) to n(Ti) = 1:25 in the final sample, cerium nitrate (Ce(NO3)3) and titanium sulfate (Ti(SO4)2) were weighed and added to deionized water. Stirred continuously on a magnetic stirrer at room temperature for 1 hour until fully dissolved to form a precursor solution. Ammonia water was slowly added dropwise to the precursor solution with continuous stirring until the pH value of the solution reached 10 and a precipitate appeared. After aging at room temperature for 12 hours, the resulting precipitate was washed with deionized water until neutral, then dried at 100°C for 12 hours, crushed and sieved, and calcined at 400°C for 5 hours to obtain a dark yellow powder, which is the composite catalyst precursor.

[0077] S2: 2g of composite catalyst precursor, 40mL of a mixed solution containing 0.5832g of hexadecyltrimethylammonium bromide (CTAB) and NaOH (wherein the concentration of NaOH is 10mol / L) were transferred to a polytetrafluoroethylene liner, ultrasonically treated for 30min, and then transferred to a magnetic stirrer and stirred for 1h to mix evenly. The mixture was placed in a stainless steel reactor and allowed to stand at 150°C and autogenous pressure for 24h to form crystals. After the reaction was completed, the reactor was taken out and cooled at room temperature. The obtained product was first washed with dilute nitric acid to a pH of about 1.6, and then repeatedly washed with deionized water and anhydrous ethanol until neutral, and then dried at 80°C for 12h. Finally, it was calcined at 400°C for 3h to obtain a composite tubular catalyst. The composite catalyst obtained in this comparative example was observed by scanning electron microscopy. The results are shown in Figure 2 .

[0078] Comparative Example 4

[0079] This comparative example provides a method for preparing a composite tubular catalyst, comprising the following steps:

[0080] S1: According to the molar ratio of n(Ce) to n(Ti) = 1:4 in the final sample, cerium nitrate (Ce(NO3)3) and titanium sulfate (Ti(SO4)2) were weighed and added to deionized water. Stirred continuously on a magnetic stirrer at room temperature for 1 hour until fully dissolved to form a precursor solution. Ammonia water was slowly added dropwise to the precursor solution with continuous stirring until the pH value of the solution reached 10 and a precipitate appeared. After aging at room temperature for 12 hours, the resulting precipitate was washed with deionized water until neutral, then dried at 100°C for 12 hours, crushed and sieved, and calcined at 400°C for 5 hours to obtain a dark yellow powder, which is the composite catalyst precursor.

[0081] S2: 2g of composite catalyst precursor, 40mL of a mixed solution containing 0.5832g of hexadecyltrimethylammonium bromide (CTAB) and NaOH (wherein the concentration of NaOH is 10mol / L) were transferred to a polytetrafluoroethylene liner, ultrasonically treated for 30min, and then transferred to a magnetic stirrer and stirred for 1h to mix evenly. The mixture was placed in a stainless steel reactor and allowed to stand at 150°C and autogenous pressure for 24h to form crystals. After the reaction was completed, the reactor was taken out and cooled at room temperature. The obtained product was first washed with dilute nitric acid to a pH of about 1.6, and then repeatedly washed with deionized water and anhydrous ethanol until neutral, and then dried at 80°C for 12h. Finally, it was calcined at 400°C for 3h to obtain a composite tubular catalyst. The composite catalyst obtained in this comparative example was observed by scanning electron microscopy. The results are shown in Figure 3 .

[0082] Experimental example

[0083] 1. Simultaneous NOx and toluene removal activity test

[0084] The catalysts obtained in Examples 1-6 and Comparative Examples 1-4 were crushed and sieved to 40-60 mesh. 0.1 g of the catalysts were weighed and placed in a fixed-bed quartz tube reactor. The conversion and selectivity of the corresponding substances of the samples were tested at 100-400° C. using a Gasmet DX4000 in a simulated flue gas atmosphere (NOx: 500 ppm, NH3: 500 ppm, toluene: 50 ppm, O2: 5 vol%, and the remainder was N2). The total gas flow rate was 100 mL / min (space velocity SV = 60000 mL·g -1 ·h -1 ). See the results for Figure 7-14 .

[0085] Figure 7-13 The graphs of toluene degradation and denitrification performance test of the composite tubular catalyst for efficient removal of NOx and VOCs prepared in Examples 1-6 and Comparative Examples 1-4 are shown respectively. Figure 12 and Figure 13 It can be seen that at 60000mL·g -1 ·h -1 At a space velocity of , the catalysts prepared in Examples 1-6 all showed excellent performance in removing NOx and toluene simultaneously. Among them, Example 3 had the best catalytic activity, and the effective degradation temperature range was 200-350 ° C (see Figure 7 The effective degradation temperature range of Comparative Example 1 is 225-325°C (see Figure 8 ), the effective degradation temperature range of Comparative Example 2 is 275-350°C (see Figure 9 ), the effective degradation temperature range of Comparative Example 3 is 225-310°C (see Figure 10 ), the effective degradation temperature range of Comparative Example 4 is 210-300°C (see Figure 11 ), compared with Comparative Examples 1-4, the collaborative removal temperature window of Example 3 is wider and the CO2 selectivity is improved.

[0086] In addition, by Figure 14 It can be seen that only a small amount of N2O is generated in Examples 1-4 and Comparative Examples 1-4 during the test process, and the samples have excellent N2 selectivity.

[0087] 2. Simultaneous removal activity test of NOx and chlorobenzene

[0088] The catalyst obtained in Example 3 was crushed and sieved to 40-60 mesh, and 0.1 g was weighed and placed in a fixed-bed quartz tube reactor. The conversion and selectivity of the corresponding substances of the sample were tested at 200-350°C using a Gasmet DX4000 in a simulated flue gas atmosphere (NOx: 500 ppm, NH3: 500 ppm, chlorobenzene: 50 ppm, O2: 5 vol%, and the remainder was N2). The total gas flow rate was 100 mL / min (space velocity SV = 60000 mL·g -1 ·h -1 ). See the results for Figure 15 .

[0089] Figure 15 This is a test chart of the degradation and denitrification performance of the composite tubular catalyst for efficient removal of NOx and VOCs prepared in Example 3. -1 ·h -1 At a space velocity of , the catalyst prepared in Example 3 exhibits excellent performance in simultaneously removing NOx and chlorobenzene, and its effective degradation temperature range is 300-350°C.

[0090] 3. Stability test of simultaneous removal of NOx and toluene

[0091] The catalyst obtained in Example 3 was crushed and sieved to 40-60 mesh, and 0.1 g was weighed and placed in a fixed-bed quartz tube reactor. The sample was continuously reacted at 250° C. for 1200 min in a simulated flue gas atmosphere (NOx: 500 ppm, NH3: 500 ppm, toluene: 50 ppm, O2: 5 vol%, and the remainder was N2) using a Gasmet DX4000 to test the conversion and selectivity of the corresponding substances. The total gas flow rate was 100 mL / min (space velocity SV = 60000 mL·g -1 ·h -1 ). See the results for Figure 16 .

[0092] 4. NOx and toluene removal and water resistance test

[0093] The catalyst obtained in Example 3 was crushed and sieved to 40-60 mesh, and 0.1 g was weighed and placed in a fixed-bed quartz tube reactor. The sample was reacted continuously at 250° C. for 600 min in a simulated flue gas atmosphere (NOx: 500 ppm, NH3: 500 ppm, toluene: 50 ppm, O2: 5 vol%, H2O: 5 vol% (when used), and the remainder was N2) using a Gasmet DX4000 to test the conversion and selectivity of the corresponding substances. The total gas flow rate was 100 mL / min (space velocity SV = 60000 mL·g -1 ·h -1 ). See the results for Figure 17 .

[0094] 5. NOx and toluene removal and sulfur water resistance performance test

[0095] The catalyst obtained in Example 3 was crushed and sieved to 40-60 mesh, and 0.1 g was weighed and placed in a fixed-bed quartz tube reactor. The sample was reacted continuously at 275° C. for 300 min in a simulated flue gas atmosphere (NOx: 500 ppm, NH3: 500 ppm, toluene: 50 ppm, O2: 5 vol%, H2O: 5 vol% (when used), SO2: 100 ppm (when used), and the remainder was N2) to determine the conversion and selectivity of the corresponding substances using a Gasmet DX4000. The total gas flow rate was 100 mL / min (space velocity SV = 60000 mL·g -1 ·h -1 ). See the results for Figure 18 .

[0096] Figure 16 These are the stability test results of the composite tubular catalyst for efficient removal of NOx and VOCs prepared in Example 3 under the conditions of continuous reaction at 250°C for 1200 minutes. Figure 17 The results of the water resistance test of the composite tubular catalyst for efficient removal of NOx and VOCs prepared in Example 3 were obtained under the conditions of continuous reaction at 250°C for 600 minutes. Figure 18 The test results of the sulfur water resistance of the composite tubular catalyst for efficient removal of NOx and VOCs prepared in Example 3 under the conditions of continuous reaction at 275°C for 300 minutes. Figure 16-Figure 18 It can be seen that the catalyst prepared by the present invention can still maintain long-term stability under complex flue gas conditions and has good industrial application prospects.

[0097] Although the principles of the present invention have been described in detail above in conjunction with the preferred embodiments of the present invention, those skilled in the art should understand that the above embodiments are merely illustrative of the present invention and are not intended to limit the scope of the present invention. The details in the embodiments do not constitute a limitation on the scope of the present invention. Without departing from the spirit and scope of the present invention, any obvious changes such as equivalent transformations and simple substitutions based on the technical solution of the present invention fall within the scope of protection of the present invention.

Claims

1. A method for preparing a composite tubular catalyst, characterized in that: The following steps are involved: S1: adding metal salt and titanium salt into deionized water and stirring to dissolve, then adding alkali solution to make the mixed solution precipitate, aging, and finally washing, drying, grinding and calcining the precipitate to obtain a composite catalyst precursor; S2: mixing the composite catalyst precursor and the strong alkaline solution, ultrasonically treating and stirring, and then subjecting them to a hydrothermal reaction, and then acid-washing and water-washing the reaction product, and finally drying, grinding and calcining to obtain the composite tubular catalyst; Wherein, the molar ratio of the metal to titanium is 0.05-0.2:

1.

2. The method for preparing the composite tubular catalyst according to claim 1, characterized in that: In the composite tubular catalyst, the molar ratio of the metal in the metal salt to the titanium in the titanium salt is 0.125:

1.

3. The method for preparing the composite tubular catalyst according to claim 1, characterized in that: In step S1, the metal in the metal salt is selected from one or more of cerium, vanadium, manganese, iron or copper; and / or, The alkali solution is selected from one or more of ammonia water, sodium hydroxide, ammonium carbonate or sodium oxalate solution.

4. The method for preparing the composite tubular catalyst according to claim 1, characterized in that: In step S1, the aging time is 12-24 hours; and / or, The calcination time is 3-5 hours and the temperature is 400-500°C.

5. The method for preparing the composite tubular catalyst according to claim 1, characterized in that: In step S2, the strong alkaline solution is one or more of sodium hydroxide or potassium hydroxide solution, with a concentration of 8-12 mol / L; and / or, The mass volume ratio of the composite catalyst precursor and the strong alkali solution is 1g:20-35mL.

6. The method for preparing the composite tubular catalyst according to claim 1, characterized in that: In step S2, the temperature of the hydrothermal reaction is 140-180° C. and the time is 24-48 hours; and / or, The calcination temperature is 400-500°C, the calcination time is 3-5 hours, and / or, The solution used for pickling is one or more of dilute nitric acid or dilute hydrochloric acid, and the pH value of the product after pickling is 1-2; and / or, The solution used for the water washing is deionized water and ethanol.

7. The method for preparing the composite tubular catalyst according to claim 1, characterized in that: In step S2, a surfactant may be added to the strong alkaline solution, wherein the surfactant is hexadecyltrimethylammonium bromide; After the surfactant is added to the strong alkaline solution, the concentration of the surfactant in the mixed solution is 0.001-0.08 mol / L.

8. A composite tubular catalyst, characterized in that: The preparation method is adopted according to any one of claims 1 to 7.

9. Use of the composite tubular catalyst according to claim 8 in the simultaneous removal of NOx and VOCs.

10. The use according to claim 9, characterized in that: The temperature range for simultaneous removal of NOx and VOCs is 100-400℃.

Citation Information

Patent Citations

  • Catalyst for CVOCs catalytic combustion and preparation method thereof

    CN109529806A

  • Composite oxide catalyst for synchronously removing VOCs (Volatile Organic Compounds) and NOx in sulfur-containing flue gas as well as preparation method and application of composite oxide catalyst

    CN114160147A

  • SCR (Selective Catalytic Reduction) catalyst for flue gas high-efficiency synergistic denitration and toluene removal as well as preparation method and application of SCR catalyst

    CN115445594A

  • Hollow nanotube-shaped catalyst as well as preparation method and application thereof

    CN116899586A

  • Nitrogen oxide and volatile organic pollutant synergistic purification catalyst and preparation method thereof

    CN118594527A

Cited By

  • Preparation method of Ce-Ti-S catalyst for efficiently removing methylbenzene and NOx at low temperature

    CN120094607A